2015
DOI: 10.1002/alr.21668
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐two–item Sino‐Nasal Outcome Test in a control population: a cross‐sectional study and systematic review

Abstract: SNOT-22 scores vary in non-CRS populations depending upon the group queried. Asthma and depression are associated with higher SNOT-22 scores and should be considered when determining what constitutes a normal value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
3
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 44 publications
1
32
3
1
Order By: Relevance
“…By postoperative visit 4, no statistical difference between SNOT-22 scores was noted between packing types. However, our scores correlate with the mean pooled baseline scores for the population without CRS (11 ± 9.4, n = 1517) and are lower than those reported by Farhood et al 35 (16.4 ± 15.2). There was a correlation between disease severity preoperatively, measured by LM scores, and SNOT-22 improvements, suggesting patients with worse disease trended toward greater, more dramatic, improvements in SNOT-22 scores postoperatively (p = 0.07), but it was not significant.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…By postoperative visit 4, no statistical difference between SNOT-22 scores was noted between packing types. However, our scores correlate with the mean pooled baseline scores for the population without CRS (11 ± 9.4, n = 1517) and are lower than those reported by Farhood et al 35 (16.4 ± 15.2). There was a correlation between disease severity preoperatively, measured by LM scores, and SNOT-22 improvements, suggesting patients with worse disease trended toward greater, more dramatic, improvements in SNOT-22 scores postoperatively (p = 0.07), but it was not significant.…”
Section: Discussioncontrasting
confidence: 81%
“…By postoperative visit 4, no statistical difference between SNOT‐22 scores was noted between packing types. However, our scores correlate with the mean pooled baseline scores for the population without CRS (11 ± 9.4, n = 1517) and are lower than those reported by Farhood et al . (16.4 ± 15.2).…”
Section: Discussioncontrasting
confidence: 80%
“…The most widely accepted and best validated patient self-report symptom evaluation tool for use in CRS is the SNOT-22, whose 22 items incorporate both nasal and non-nasal symptoms (Hopkins,5,6 Within SNOT-22, self-reported symptom severity is graded from 0 to 5, with five being a severe problem. 12 The overarching aim of the Chronic Rhinosinusitis Epidemiology Study (CRES) was to aid better understanding of medical and non-medical factors contributing to development or worsening of CRS. 7 Factor analysis identifies four principal SNOT domainsnasal, facial, sleep and mood 8 .…”
Section: Resultsmentioning
confidence: 99%
“…First, greater than one third of our study cohort did not achieve an MCID of SNOT‐22 scores, suggesting that, although pre‐ and posttreatment symptom scores were statistically significantly different, many patients may not have noted a clinically detectable benefit. In addition to the significantly higher SNOT‐22 score of the posttreatment cohort as compared with healthy controls, the posttreatment scores in this study were nearly 2 MCIDs higher than the literature reported mean SNOT‐22 scores of control patients, which can serve as a surrogate for CRS patients with a return to “normal.” Finally, although heterogeneous in nature, several studies have suggested that medical therapy confers a variable rate of success after AMT ranging from 14% to 65%, with success defined by either patients not requiring operative intervention or binary patient‐reported symptom improvement . With this in mind, if the cohort in this study was followed longitudinally, one could expect that a subset of this medically treated group would ultimately require surgical intervention.…”
Section: Discussionmentioning
confidence: 98%